PREVALENCE IDENTIFICATION AND ANTIFUNGAL SUSCEPTIBILITY OF DERMATOPHYTES CAUSING TINEA CAPITIS IN A LOCALITY IN NORTH CENTRAL NIGERIA - Ekundayo, Ayodele Halimat; Charles, Nwabuisi; Abayomi, Fadeyi (African Journal of Infectious Diseases (AJID), 2020)
Background: Tinea capitis impacts negatively on the health of children, consequently affecting their education. Its prevalence is unknown in many African communities. Tinea capitis is faced with therapeutic challenges as resistance to all classes of antifungal agents continues to emerge. This study determined the prevalence, identified dermatophytes of tinea capitis in Okelele community in North Central Nigeria and evaluated the susceptibility of isolates to selected antifungal drugs. Materials and Methods: Three hundred and one pupils from seven primary schools in the locality who gave assent and those with parental consent were recruited into the study. Scalp scrapings and hairs were collected from participants and subjected to microscopy and culture. Isolates identified by colonial morphology and micromorphology were subjected to disk diffusion antifungal susceptibility testing. Results: Two hundred and twenty-eight of the participants had mycologically proven tinea capitis giving a prevalence of 75.7%. The dermatophytes identified were T. rubrum (68.0%), M. ferrugineum (22.0%), T. mentagrophytes (8.0%) and T. verrucosum (2.0%). Resistance observed with these isolates was as low as 21.2% to as high as 100% while sensitivity ranged from 78.8% to 100%. Only large family size significantly influenced the occurrence of tinea capitis among the risk factors. Conclusion: The prevalence of tinea capitis from this study is high. T. rubrum being anthropophilic and the predominant dermatophyte identified corroborates large family size as an important risk factor. Antifungal resistance as a cause of therapeutic failure was demonstrated by some isolates in this study.